Incidence of Metabolic Syndrome from Atypical Antipsychotic Therapy in Schizophrenia Patients - Utami, Indah K. (Universitas Padjadjaran, Indonesia, 2025)
Schizophrenia is a psychiatric disorder impacting behavior, emotions, and communication. Atypical antipsychotics are increasingly prescribed due to their significant reduction of both positive and negative symptoms and low risk of extrapyramidal side effects (EPS) in schizophrenia patients. However, long-term effects of atypicals may include weight gain, insulin resistance, and hyperglycemia. This study was conducted in Palu, Madani General Hospital, and Anutapura General Hospital. It used a prospective cross-sectional design with a sample of 40 outpatient participants who received monotherapy or combination therapy with clozapine, olanzapine, and risperidone for more than three months. Blood samples were collected to determine the presence of metabolic syndrome, defined as meeting at least three of the following five criteria: BMI > 30 kg/m², blood pressure ≥ 130/85 mmHg, triglycerides ≥ 150 mg/dL, HDL ≤ 40 mg/dL, and fasting blood glucose ≥ 110 mg/dL. The prevalence of metabolic syndrome was (25%), pre-metabolic syndrome (37,5%), and non-metabolic syndrome (37,5%) with a significance value of 0,5 > 0,05. The percentage of schizophrenia patients by gender was dominated by males (58%). Age-wise, adults dominated the sample (77.5%). Risperidone was the most frequently used atypical antipsychotic (56%). The most common concomitant medications were antimuscarinics (29.6%). The use of atypical antipsychotics did not significantly impact the side effects associated with metabolic syndrome with a p-value 0,5 > 0,05. However, there was an increase in the values for one or two of the five criteria for metabolic syndrome in schizophrenia patients. Future research should consider using only olanzapine or clozapine monotherapy for medication criteria.